Pentingnya Konsep Dasar Supervisi Pendidikan (The Importance and Basic Concepts of Educational Supervision) - Rendyka Eliadi; Nazyumei Arbah; Fauzi Rahman; Ambiyar Ambiyar; Mahesi Agni Zaus (Journal on Education, 2023)
This research was conducted with the aim of showing how important the basic concept of educational supervision is to improving the quality of education. Educational supervision has a very significant role in improving the quality of education. The basic concept of educational supervision covers various aspects, such as the purpose of supervision, the process of supervision, the relationship between supervisors and teachers, supervision techniques, the competence of supervisors, and the focus on student learning. The main purpose of educational supervision is to ensure that educational goals are achieved and students can achieve their best potential. The supervision process involves supervising, directing, and coaching teachers or teaching staff to help them develop professional skills, solve problems, and improve the quality of learning in the classroom. By implementing the basic concepts of proper educational supervision, it is expected to be able to create an effective, efficient learning environment and improve the overall quality of education.